Effect of Using Plastic Waste Bottles on Soil Response above Buried Pipes under Static Loads - Sinan A. Al-Haddad; Faris H. Al-Ani; Mohammed Y. Fattah (Applied Sciences, 2022)
Development and population growth have made using shallow buried pipes in urban areas, highways, and subways inevitable. In this study, the performance and behavior of shallow unplasticized polyvinyl chloride (uPVC) pipes buried in sand reinforced with PET (polyethylene terephthalate) bottles produced by the end consumer filled with soil under static loads were investigated. The bottle reinforcement mattress filled with soil was vertically installed above the buried uPVC pipe inside the soil bed at the required depth; after that, backfilling was performed. The effects of the relative density of soil, placement depth, and the width of the soil-filled bottle-reinforced block were examined. The increase in relative density has shown a noticeable decrease in footing surface settlement and load transferred to the buried pipe. The test results have shown significant improvement in the ultimate bearing capacity of bottle-reinforced soil with a reduction in surface settlement. The backfill reinforced with soil-filled bottle block has shown a 71% improvement in ultimate bearing capacity. Additionally, the improvement in bearing capacity increases as the placement depth decreases and width increases. The optimum depth of placement and width of the bottle-reinforced mattress were 0.50 and 2.08 B. The proposed soil reinforcement method may be a good and relatively inexpensive alternative to traditional geosynthetic reinforcement while providing geotechnical and environmental benefits.